THE SOCIO-ECONOMIC SIGNIFICANCE OF WOMEN’S ENTREPRENEURSHIP IN UZBEKISTAN - Oybek Batirov (Modern American Journals, 2025)
This paper explores the socio-economic importance of women’s entrepreneurship in Uzbekistan. It investigates how female-led enterprises contribute to employment creation, poverty reduction, and inclusive growth. Drawing upon data from 2016 to 2024 and international experiences, the study reveals key trends in gender participation, sectoral distribution, and barriers affecting women entrepreneurs. The findings indicate that while female participation in entrepreneurship is growing, structural challenges such as limited access to finance and market networks persist. The paper concludes by proposing policy recommendations to enhance women’s economic empowerment and support sustainable business development.
Keywords: Women entrepreneurship, Uzbekistan, socio-economic development, gender equality, business policy, employment.